Collaboration Between Government Agencies: Challenges and Opportunities in Public Policy Implementation - Arnika, Mita; Rifdan, Rifdan; Arief, Muhammad Makka; Halid, A Abd waris; Taufik, Andi; Hasrini, Sry (Program Pascasarjana Universitas Negeri Makassar, 2024)
This study aims to analyze the challenges and opportunities in inter-agency collaboration in the implementation of public policy in Indonesia. Based on in-depth interviews with officials from the Ministry of Environment and Forestry (KLHK), Ministry of Energy and Mineral Resources (ESDM), Ministry of Health, and the Social Security Agency (BPJS), as well as analysis of related policy documents, the study identifies several key challenges in collaboration, such as differing priorities between agencies, lack of coordination, and bureaucratic fragmentation that slows decision-making. Additionally, opportunities for improving collaboration were found, including the use of information and communication technology (ICT), data-driven policies, and enhancing the capacity of government officials in managing inter-agency relationships. The findings suggest that effective collaboration requires strengthened communication, more structured policy formulation, and improved coordination between central and regional governments. This study provides recommendations for improving the effectiveness of inter-agency collaboration to achieve more optimal and sustainable public policies.